1999
DOI: 10.1128/jvi.73.10.8527-8540.1999
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Gag Polyprotein Multimerization Requires the Nucleocapsid Domain and RNA and Is Promoted by the Capsid-Dimer Interface and the Basic Region of Matrix Protein

Abstract: The human immunodeficiency virus type 1 (HIV-1) Gag polyprotein directs the formation of virions from productively infected cells. Manygag mutations disrupt virion assembly, but little is known about the biochemical effects of many of these mutations. Protein-protein interactions among Gag monomers are believed to be necessary for virion assembly, and data suggest that RNA may modify protein-protein interactions or even serve as a bridge linking Gag polyprotein monomers. To evaluate the primary sequence requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(64 citation statements)
references
References 64 publications
6
58
0
Order By: Relevance
“…3) agrees with the proposal that RNA (viral or nonspecific) is required for mediating hA3G-Gag association and hA3G incorporation into virions (Svarovskaia et al, 2004;Zennou et al, 2004). We assumed that the chimeras considered competent in hA3G packaging are capable of packaging considerable amounts of RNA, since the SARS-CoV N (Hsieh et al, 2005;Luo et al, 2006) and HIV-1 MA domains (Burniston et al, 1999;Ott et al, 2005) both possess nucleic acid binding properties that may confer RNA packaging ability. Using a RNA quantification assay as described by Chang et al (2008), we found that NC(N2) VLPs contain RNA at approximately 80% of the level measured in HIV-1 Gag VLPs (data not shown).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…3) agrees with the proposal that RNA (viral or nonspecific) is required for mediating hA3G-Gag association and hA3G incorporation into virions (Svarovskaia et al, 2004;Zennou et al, 2004). We assumed that the chimeras considered competent in hA3G packaging are capable of packaging considerable amounts of RNA, since the SARS-CoV N (Hsieh et al, 2005;Luo et al, 2006) and HIV-1 MA domains (Burniston et al, 1999;Ott et al, 2005) both possess nucleic acid binding properties that may confer RNA packaging ability. Using a RNA quantification assay as described by Chang et al (2008), we found that NC(N2) VLPs contain RNA at approximately 80% of the level measured in HIV-1 Gag VLPs (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…In addition to playing a key role in viral RNA packaging (Berkowitz et al, 1993(Berkowitz et al, , 1995Poon et al, 1996;Zhang and Barklis, 1997), NC contains an I domain that is responsible for Gag-Gag interactions (Bennett et al, 1993;Bowzard et al, 1998). Heterologous polypeptides capable of self-association have been shown to confer the ability to efficiently produce chimeric VLPs when substituted for HIV-1 NC (Accola et al, 2000;Burniston et al, 1999;Johnson et al, 2002;Zhang et al, 1998). However, replacing NC with a leucine-zipper motif that does not encapsidate RNA abolishes hA3G packaging without significantly affecting HIV-1 virion production (Zennou et al, 2004), suggesting RNA involvement in hA3G incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…This proposed mechanism stipulates that binding of several justmade GagNC molecules to the Packaging region of the FL viral RNA would render it inaccessible to translating ribosomes due to structural rearrangements of the 5 UTR such as base pairing interactions involving the Gag AUG initiation codon (Abbink and Berkhout, 2003;Berkhout, 1996;D'Souza and Summers, 2004;Lu et al, 2011a,b). This together with bound Gag molecules Berkhout, 2001a,b, 2002) would cause a functional reorientation of the FL RNA from translation to dimerization and packaging (Heng et al, 2012) effectively starting Gag assembly where the FL RNA acts as the initial platform or scaffold (Burniston et al, 1999;Cimarelli et al, 2000;Muriaux et al, 2001;Ott et al, 2009;reviewed in Butsch andBoris-Lawrie, 2000, 2002;Darlix et al, 1995Darlix et al, , 2000. As a result of the nucleation event is the targeting of the viral Gag-RNP complex to cellular membranes due to another conformational switch at the opposite end of Gag.…”
Section: Nc the Nucleation Of Retrovirus Assembly And Structure Switmentioning
confidence: 99%
“…Results from a previous study show that HIV-1 NC facilitates Pr55 gag membrane association [39]. Furthermore, most Gag mutants (either multimerization-defective or assembly-defective) demonstrate markedly reduced membrane binding capacities [9,15,23]. We performed membrane flotation experiments to test whether the replacement of HIV-1 NC by SARS-CoV N exerts any effect on membrane binding, and to determine if the assembly defect is correlated with reduced membranebinding capacity.…”
Section: Membrane Flotation Analysis Of Chimeric Proteinsmentioning
confidence: 99%
“…Likewise, recombinant SARS-CoV nucleocapsid proteins can undergo multimerization via self-association [16,30,42,51]. Since heterologous polypeptides that form interprotein contacts permit efficient VLP production when placed in the HIV-1 NC region [1,9,20,54], we initially tested whether SARS-CoV N substitution for HIV-1 NC supports chimeric VLP assembly and release, and found that HIV-1 Gag mutants containing SARS-CoV N coding sequences as NC substitutes are capable of VLP assembly. This suggests that the HIV-1 NC assembly domain can be functionally replaced with the SARS-CoV N.…”
Section: Introductionmentioning
confidence: 99%